Cardiovascular outcomes with glucagon-like peptide-1 receptor agonists in patients with type 2 diabetes: a meta-analysis. Issue 2 (February 2018) - Bethel, M Angelyn; Patel, Rishi A; Merrill, Peter; Lokhnygina, Yuliya; Buse, John B; Mentz, Robert J; Pagidipati, Neha J; Chan, Juliana C; Gustavson, Stephanie M; Iqbal, Nayyar; Maggioni, Aldo P; Öhman, Peter; et al.
Summary: Background: Glucagon-like peptide-1 (GLP-1) receptor agonists are effective glucose-lowering drugs. Findings from cardiovascular outcome trials showed cardiovascular safety of GLP-1 receptor agonists, but results for cardiovascular efficacy were varied. We aimed to examine overall cardiovascular efficacy for lixisenatide, liraglutide, semaglutide, and extended-release exenatide. Methods: In this systematic review and meta-analysis, we analysed data from eligible trials that assessed the safety and efficacy of GLP-1 receptor agonists compared with placebo in adult patients (aged 18 years or older) with type 2 diabetes and had a primary outcome including, but not limited to, cardiovascular mortality, non-fatal myocardial infarction, and non-fatal stroke. We searched PubMed and MEDLINE without language restrictions up to Sept 18, 2017, for eligible trials. We did a meta-analysis of available trial data using a random-effects model to calculate overall hazard ratios (HRs) for cardiovascular efficacy outcomes and odds ratios for key safety outcomes. Findings: Of 12 articles identified in our search and screened for eligibility, four trials of cardiovascular outcomes of GLP-1 receptor agonists were identified: ELIXA (lixisenatide), LEADER (liraglutide), SUSTAIN 6 (semaglutide), and EXSCEL (extended-release exenatide). Compared with placebo, GLP-1 receptor agonist treatment showed a significant 10% relative risk reduction in the three-point major adverse cardiovascular event primary outcome (cardiovascular mortality, non-fatal myocardial infarction, and non-fatal stroke; HR 0·90, 95% CI 0·82–0·99; p=0·033), a 13% RRR in cardiovascular mortality (0·87, 0·79–0·96; p=0·007), and a 12% relative risk reduction in all-cause mortality (0·88, 0·81–0·95; p=0·002), with low-to-moderate between-trial statistical heterogeneity. No significant effect of GLP-1 receptor agonists was identified on fatal and non-fatal myocardial infarction, fatal and non-fatal stroke, hospital admission for unstable angina, or hospital admission for heart failure. Overall, no significant differences were seen in severe hypoglycaemia, pancreatitis, pancreatic cancer, or medullary thyroid cancer reported between GLP-1 receptor agonist treatment and placebo. Interpretation: Our findings show cardiovascular safety across all GLP-1 receptor agonist cardiovascular outcome trials and suggest that drugs in this class can reduce three-point major adverse cardiovascular events, cardiovascular mortality, and all-cause mortality risk, albeit to varying degrees for individual drugs, without significant safety concerns. GLP-1 receptor agonists have a favourable risk–benefit balance overall, which should allow the choice of drug to be individualised to each patient's needs. Funding: Amylin Pharmaceuticals (AstraZeneca).